1997
DOI: 10.1097/00000421-199702000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Intrathoracic Recurrence of Non-Small Cell Lung Cancer

Abstract: Fifty-two of 2,315 patients (2.4%) with non-small cell lung cancer (NSLC) treated with radiation therapy at the Mallinckrodt Institute of Radiology and St. Luke's Hospital between 1975 and 1988 presented with local recurrence after definitive surgery. No patient received radiation therapy after surgery as part of initial treatment and none had evidence of distant metastases at the time of local recurrence. The median time to first recurrence was 14 months. At recurrence, patients presented with disease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
2
15
2
Order By: Relevance
“…The 5-year and median OS results for those with recurrence in our study appeared to be better than those reported by others, which have ranged from 4% to 12.5% and 8.1 to 14.0 months, respectively (9)(10)(11)(12)(13)(14)(15)(16)(17), and the survival of the newly diagnosed patients was comparable to those reported for 1996-2004 in the 17 Surveillance, Epidemiology, and End Results geographic areas (5-year survival rate, 15.2%; available from: http://seer.cancer.gov/statfacts/html/lungb. html).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…The 5-year and median OS results for those with recurrence in our study appeared to be better than those reported by others, which have ranged from 4% to 12.5% and 8.1 to 14.0 months, respectively (9)(10)(11)(12)(13)(14)(15)(16)(17), and the survival of the newly diagnosed patients was comparable to those reported for 1996-2004 in the 17 Surveillance, Epidemiology, and End Results geographic areas (5-year survival rate, 15.2%; available from: http://seer.cancer.gov/statfacts/html/lungb. html).…”
Section: Discussioncontrasting
confidence: 80%
“…The prognostic factors for survival of postresection recurrent NSCLC patients have been studied by other investigators. Emami et al (12) reported the best indicators for longterm survival in 52 postresection recurrent patients were the interval from initial surgery to the first recurrence (p <.001) and the tumor response to RT (p = .014). Jeremic et al (14) found that in 61 postresection recurrent NSCLC patients, those treated with high-dose RT (radical intent) had better survival than patients treated with low-dose RT (palliative intent; p <.001); women had better survival than men (p = .02); and the stage and location of the recurrence were also significant prognostic factors (p = .0016 and p = .0011, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Walsh et al (23) characterized disease-free interval as an “indirect measure of a patient’s tumor biology and aggressiveness”. Thus, longer disease-free interval has been reported to be associated with prolonged survival following recurrence in several studies (2427). …”
Section: Discussionmentioning
confidence: 99%
“…2-5 For locoregional recurrence, radiation therapy is the treatment of choice, and several reports have shown that 2-and 5-year survival is comparable to those for radiation therapy alone in patients with primary stage III non-small cell lung cancer. [6][7][8] Therefore, we have treated these patients with radical radiation therapy when possible.…”
Section: Introductionsmentioning
confidence: 99%